Design and Optimization of Chronotherapeutic Dosage Form for the Treatment of Angina Pectoris - Singh, Rupali; Malviya, Rishabha (Drug Delivery Letters, 2021)
Background: The chronotherapy concept attains considerable focus towards itself due to its pulsatile fashion rather than continuous delivery. The delivery of the right amount of drug to the target organ at the most appropriate time is fulfilled by using the chronotherapeutic dosage form. Aim: The present study aims to develop and evaluate a chronotherapeutic drug delivery system by using natural polymer for time-specific drug delivery at the target site. Methods: Tamarind seed polysaccharide was extracted and used in the preparation of core tablets. Nine formulations of core tablets were prepared with nifedipine at 5 tonnes of pressure on a 6 mm punch. The core tablets were prepared by using the compression coating method. The three batches F1, F2, and F3 were prepared by using tamarind gum in different concentrations i.e., 45%, 22.5%,and 67.5%, respectively, and compressed at 8 tonnes of pressure on 12 mm of punch. The finally compressed tablet was coated with different concentrations of ethyl cellulose in which isopropyl alcohol was used as a solvent. In a controlled medium, a stability study was performed to evaluate the physical appearance, drug content, and release of the prepared core tablet. Result and Discussion: All the nine formulations of tablets were prepared successfully and the evaluation studies (thickness, weight variation, hardness, friability, etc.) revealed that all the formulations were within the official range. The release study of the drug revealed that the formulation F7 containing 67.5% of tamarind polymer, coated with 2%, 4%, and 5% of ethylcellulose solution released 59.68 ± 1.03% (Q50%) drug within 5 h whereas 87.09 ± 2.08% (Q80%) within 6 h and 97.74 ± 2.19% of the drug was released within 12 h. The formulation F7 was found to be more effective as it released the maximum amount of drug in a short period as compared to other formulations. Conclusion: The coating of core tablets allowed to prepare pharmaceutical dosage form for timespecific drug delivery. These chronotherapeutic core tablets can be used for the treatment of angina pectoris and hypertension, etc.
Keywords: formulation optimization